ON THE DYNAMICS OF THE HARMONIC OSCILLATING AND MOVING STRIP LOAD ACTING ON THE SYSTEM CONSISTING ON THE PRE-STRESSED COVERING LAYER AND PRE-STRESSED HALF-PLANE - Ilhan, Nihat; Akbarov, Surkay (AMER SOC MECHANICAL ENGINEERS, 2010)
This paper investigates the dynamic response to a time-harmonic oscillating moving strip load of a system comprising an initially stressed covering layer and initially stressed half-plane, within the scope of the piecewise homogeneous body model utilizing three-dimensional linearized wave propagation theory in the initially stressed body It is assumed that the materials of the layer and half-plane are anisotropic (orthotropic), and that the velocity of the line-located time-harmonic oscillating moving load is constant as it acts on the free face of the covering layer. Our investigations were carried out for a two dimensional problem (plane-strain state) under subsonic velocity for a moving load in complete and incomplete contact conditions. The corresponding numerical results were obtained for the stiffer layer and soft half-plane system in which the modulus of elasticity of the covering layer material (for the moving direction of the load) is greater than that of the half-plane material Numerical results are presented and discussed for the critical velocity and stress distribution for various values of the problem parameters. In particular, it was established that the critical velocity of the moving load is controlled mainly with a Rayleigh wave speed of a half-plane material and the initial stretching of the covering layer causes these values to increase Moreover, it was established that with the oscillating frequency of the moving load, the values of the critical velocity decrease
Keywords: STRESS-FIELD; SPACE; VIBRATIONS; TRAIN; Engineering